Delineating the impacts of air temperature and humidity for endurance exercise. Issue 2 (20th December 2022) - Jenkins, Elliott J.; Campbell, Holly A.; Lee, Jason K. W.; Mündel, Toby; Cotter, James D.
Abstract : New Findings: What is the central question of this study? What are the independent effects of air temperature and humidity on performance, physiological and perceptual responses during endurance exercise? What is the main finding and its importance? When examined independently, elevated air temperature increased heat strain and impaired aerobic exercise performance, but to a lesser extent than has been reported previously. These findings highlight the importance of absolute humidity relative to temperature when exercising or working under severe heat stress. Abstract: Many studies have reported that ambient heat stress increases physiological and perceptual strain and impairs endurance exercise, but effects of air temperature per se remain almost unexamined. Most studies have used matched relative humidity, thereby exponentially increasing absolute humidity (water content in air) concurrently with temperature. Absolute (not relative) humidity governs evaporative rate and is more important at higher work rates and air temperatures. Therefore, we examined the independent effects of air temperature and humidity on performance, thermal, cardiovascular and perceptual measures during endurance exercise. Utilizing a crossover design, 14 trained participants (7 females) completed 45 min fixed‐intensity cycling (70% V ̇ O 2 peak ${\dot V_{{{\rm{O}}_{\rm{2}}}{\rm{peak}}}}$ ) followed by a 20‐km time trial in each of four environments: three air temperatures at matched absolute humidity (Cool, 18°C; Moderate, 27°C; and Hot, 36°C; at 1.96 kPa, air velocity ∼4.5 m/s), and one at elevated humidity (Hot Humid, 36°C at 3.92 kPa). Warmer air caused warmer skin (0.5°C/°C; P  < 0.001), higher heart rate (1 bpm/°C; P  < 0.001), sweat rate (0.04 l/h/°C; P  < 0.001) and thermal perceptions during fixed‐intensity exercise, but minimally affected core temperature (<0.01°C/°C; P  = 0.053). Time‐trial performance was comparable between Cool and Moderate (95% CI: –1.4, 5.9%; P  = 0.263), but 3.6–6% slower in Hot (95% CI: ±2.4%; P  ≤ 0.006). Elevated humidity increased core temperature ( P  < 0.001), perceived temperature and discomfort but not skin temperature or heart rate, and reduced mean blood pressure ( P  = 0.046) during fixed‐intensity exercise. Elevated humidity impaired time‐trial performance by 3.4% (95% CI: ±2.2%; P  = 0.006). In conclusion, these findings quantify the importance of absolute humidity alongside air temperature when exercising under severe heat stress.